The Effect of Microbes and Fly Ash to Improve Concrete Performance - Adlizie Rifkianda Muhammad; Januarti Jaya Ekaputri; Makno Basoeki (JACEE (Journal of Advanced Civil and Environmental Engineering), 2021)
This paper presents the application of fly ash combining with microbes in concrete to reduce cement content. A class F fly ash as cement replacementwas applied with ratios of 20%, 30%, 40%, and 50% to reduce hydration heat. Microbes from bacterial consortium were applied to as the filler to increase concrete compressive strength. The concrete mix design from SNI 03–2834–2000 was applied for a compressive strength target of 30 MPa. The mechanical test was carried out consisting compressive and tensile test. Concrete workability and the heat hydration measurement were performed for fresh concrete. The results showed that the maximum strength of 45.10 MPa was obtained from specimens with 30% fly ash content. Application of microbes associated with fly ash content of 40% showed the maximum strength of 48.47 MPa. It was found that the tensile strength also increased with the application of fly ash and microbes. Hydration temperature of concrete decreased with the increase of the ash content. This proves that the application of fly ash and microbes in concrete can reduce the cement as well as increasing the concrete performance.